Candidatus Rickettsia senegalensis in Cat Fleas (Siphonaptera: Pulicidae) Collected from Dogs and Cats in Cauca, Colombia. Issue 2 (16th October 2019) - Betancourt-Ruiz, Paola; Martínez-Díaz, Heidy-C; Gil-Mora, Juliana; Ospina, Catalina; Olaya-M, Luz-Adriana; Benavides, Efraín; Bolaños, Eliana; Cuervo, Claudia; Blanton, Lucas; Hidalgo, Marylin
Abstract: Rickettsia typhi and Rickettsia felis (Rickettsiales: Rickettsiaceae) are flea-transmitted pathogens. They are important causes of acute febrile illness throughout the world. We, therefore, sought to identify the rickettsial species present in the fleas of dogs and cats in the department of Cauca, Colombia. In this study, we collected 1, 242 fleas from 132 dogs and 43 fleas from 11 cats. All fleas were morphologically identified as Ctenocephalides felis (Bouché) adults and organized in pools for DNA extraction (234 pools from dogs and 11 from cats). The gltA gene from rickettsiae was targeted for screening amplification using conventional PCR. In total, 144 of the 245 pools (58.7%) were positive. The positive samples were then processed for the amplification of the 17kDa antigen gene (144/144; 100% positive) and sca5 gene (140/144; 97.2% positive). In addition, restriction enzyme length polymorphism analysis using Nla IV on the amplified product of the sca5 gene demonstrated several organisms: 21/140 (15%) were R. felis, 118/140 (84.3%) were Rickettsia asemboensis, and 1/140 (0.7%) were Candidatus Rickettsia senegalensis. Subsequent sequencing confirmed Candidatus Rickettsia senegalensis in C. felis collected from dogs the first reported from Colombia.